Gender- and obesity-specific effect of apolipoprotein C3 gene (APOC3)-482C>T polymorphism on triglyceride concentration in Turkish adults - Coban, Neslihan; Onat, Altan; Guclu-Geyik, Filiz; Komurcu-Bayrak, Evrim; Sansoy, Vedat; Hergenc, Gulay; Can, Gunay; Erginel-Unaltuna, Nihan (WALTER DE GRUYTER GMBH, 2012)
Background: Apolipoprotein C3 (APOC3) gene polymorphisms are associated with cardiometabolic risk factors, varying in ethnicities. This study aimed to investigate such association between the APOC3 -482C>T polymorphism and cardiometabolic risk factors in the turkish adult risk factor (TARF) study cohort, stratifying by gender and obesity. Methods: Randomly selected 1548 individuals (757 male and 791 female, mean age 49.9 +/- 11.8 years) were genotyped for -482C>T polymorphism using hybridization probes in a Real-Time PCR LC480 device. Results: The -482TT genotype prevailed 9.9% in men and 11.5% in women. Association between 482C>T polymorphism and dyslipidemia (p=0.036, OR=1.42, 95% CI=1.02-1.97) was found only in men. Analysis of variance showed that anthropometric and metabolic variables were not differently distributed in APOC3 -482C>T genotypes in the study population. In relation to dyslipidemia and obesity, the -482C>T polymorphism showed significant gender-by-genotype interactions (p<0.01). When the study population was stratified according to gender and obesity, homozygotes for the T allele were associated strongly with (by 45%) elevated fasting triglyceride concentrations in obese men (p=0.009) and homeostatic model assessment (HOMA) index in non-obese women (p=0.013). Furthermore, in the same subgroups, the associations of the fasting triglyceride concentrations and HOMA index with the IT genotype remained after adjustment for risk factors (p<0.05). Conclusions: APOC3 -482TT genotype is independently associated with elevated fasting triglyceride concentrations in obese men. Presence of obesity seems to be required for this genotype to induce markedly elevated triglycerides. Furthermore, it is associated with the dyslipidemia in men, without requirement of obesity.
Keywords: apolipoprotein C3-482C > T polymorphism; fasting triglyceride; gender difference; obesity; Turkish population; METABOLIC SYNDROME; LIPOPROTEIN METABOLISM; CARDIOVASCULAR-DISEASE; INSULIN-RESISTANCE; ABDOMINAL OBESITY; APOC3 GENE; RISK; VARIANTS; ASSOCIATION; GLUCOSE; Medical Laboratory Technology